Amyloid beta associations with connected speech in cognitively unimpaired adults. Issue 1 (27th May 2021) - Mueller, Kimberly D.; Van Hulle, Carol A.; Koscik, Rebecca L.; Jonaitis, Erin; Peters, Cassandra C.; Betthauser, Tobey J.; Christian, Bradley; Chin, Nathaniel; Hermann, Bruce P.; Johnson, Sterling
Abstract: Introduction: Connected speech and language (CSL) decline has been associated with early cognitive decline, but associations between CSL and Alzheimer's disease (AD) biomarkers remain a gap in the literature. Our goal was to examine associations with amyloid beta (Aβ) and longitudinal CSL trajectories in cognitively unimpaired adults at increased AD risk. Methods: Using data from the Wisconsin Registry for Alzheimer's Prevention, CSL measures were automatically extracted from digitally recorded picture descriptions. Positron emission tomography determined Aβ status. Linear mixed effects models assessed the interaction between age and Aβ on CSL trajectories. Results: Participants who were Aβ positive experienced more rapid decline on specific word content, when controlling for age, sex, and literacy. There were no differences between groups in lexical diversity measures over time. Discussion: These results indicate that declines in connected speech may be related to preclinical AD. CSL may be a promising, inexpensive, and easy‐to‐collect digital cognitive marker for AD studies.